Економіко-статистичний аналіз конкурентоспроможності малого підприємництва - Карпій, О. П.; Стадник, М. Є.; Karpii, O. P.; Stadnyk, M. Ye. (Видавництво Львівської політехніки, 2023)
Висвітлено роль малого підприємництва у ринковій економіці на сучасному етапі її розвитку, охарактеризовано його переваги та недоліки. Визначено суть поняття "конкурентоспроможність". Встановлено значення економіко-статистичного аналізу для дослідження конкурентоспроможності малого підприємництва та формування на основі цього ефективної стратегії її підвищення. За допомогою економіко-статистичних методів проаналізовано стан та динаміку становлення, розвитку і місця на ринку малого підприємництва; проаналізовано динаміку кількості малих та мікропідприємств, чисельності зайнятих у них працівників, обсягу реалізованої продукції (товарів, послуг) та їх частку на ринку за зазначеними показниками; досліджено зміну структури обсягу реалізованої продукції (товарів, послуг) підприємств усіх розмірів за видами економічної діяльності та зміну структури капітальних інвестицій малих та мікропідприємств в Україні. Охарактеризовано основні чинники, що сприяють або гамують розвиток малого підприємництва.

The article discusses the small businesses role in the market economy at the current stage of its development, characterizes its advantages and disadvantages, and defines the essence of the "competitiveness" concept. The authors have emphasized the economic and statistical analysis importance in researching the competitiveness of small businesses and in forming an effective strategy for its enhancement. Using economic and statistical methods such as absolute and relative indicators, averages, and the analysis of dynamic series, the article analyzes the state and dynamics of the formation, development, and market position of small businesses. It examines the dynamics of the small and micro-enterprises number, the employees number, the goods and services sold volume, and their market share based on these indicators. Additionally, the study investigates changes in the structure of the goods and services sold volume by all sizes enterprises according to economic activity types and changes in the capital investments structure in small and micro-enterprises in Ukraine. Furthermore, the article establishes patterns in the development of societal phenomena and processes over time, the elements distribution in statistical populations, structural shifts over time and space. The main factors contributing to or hindering the small businesses development are characterized. Based on the results of the analysis, trends in the small and micro-enterprises development in the Ukrainian market and changes in their competitive positions are outlined. Key factors that contribute to the growth of small and micro-enterprises competitiveness are identified, as well as factors that impede it. This information can serve as an important foundation for the development of an effective strategy for enhancing the small businesses competitiveness in modern conditions.
Economic and statistical small business competitiveness analysis
Keywords: конкурентоспроможність; ринок; економіка; мале підприємництво; маркетинг; економіко-статистичний аналіз; статистика; аналіз; дослідження; competitiveness; market; economics; small business; marketing; economic and statistical analysis; statistics; analysis; research; 339.137; 658.114; 311